Benzedeiras e benzidos: processos de cura e promoção de saúde mental através de benzimento - Menezes, Wanusa Almeida (2024)
This study aims to understand the demand for the services of women healers (benzedeiras) in promoting the mental health of those who seek them. The reasons people turn to these women range from headaches to discouragement and apathy (the latter commonly referred to as "espinhela caída"). It was important to demonstrate the significance of healing as a mode of care, especially concerning mental health. We also highlighted the importance of such studies for the field of Religious Studies. A relationship between folk medicine and technical medicine was developed, and an analytical history of the relationship between women, the sacred, and folk medicine was traced up to the healers. Fieldwork was conducted in which both healers and seekers were interviewed, which was crucial for understanding how the act of blessing is perceived in contemporary times across various regions of the State of Sergipe.